2023
DOI: 10.3280/riss2022-002020
|View full text |Cite
|
Sign up to set email alerts
|

Risk-orientated management in the sustainable economic system of united agricultural enterprises

Abstract: The relevance of the research is due to the need to modernization of the risk man-agement process of agricultural enterprises and their associations. In this regard, this article is aimed to develop areas for implementation of risk-oriented manage-ment of united agricultural enterprises in order carrying out a comprehensive diag-nosis of economic risks in the economic system of entities and timely identifica-tion of threats to sustainable economic development under uncertainty of macro-, and microenvironment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…However, the modern realities in which the vast majority of Ukrainians live and work testify to the need to adapt business to the functioning and conduct of its activities in wartime in order to bring Ukraine closer to victory. State support of business during the economic downturn plays an important role for its development and further functioning (Trusova et al, 2020;Kubiczek and Derej, 2021;Niyazbekova et al, 2021). Conceptual approaches to the interpretation of the peculiarities of state financial support for small businesses during the coronavirus pandemic were studied by Ukrainian scientists V. Humeniuk et al (2021), which revealed the importance of small business in solving economic and social problems of social development, the influence of state financial support in the countries of the European Union (EU), and also determined the common features and differences of state regulation of entrepreneurship.…”
Section: Discussionmentioning
confidence: 99%
“…However, the modern realities in which the vast majority of Ukrainians live and work testify to the need to adapt business to the functioning and conduct of its activities in wartime in order to bring Ukraine closer to victory. State support of business during the economic downturn plays an important role for its development and further functioning (Trusova et al, 2020;Kubiczek and Derej, 2021;Niyazbekova et al, 2021). Conceptual approaches to the interpretation of the peculiarities of state financial support for small businesses during the coronavirus pandemic were studied by Ukrainian scientists V. Humeniuk et al (2021), which revealed the importance of small business in solving economic and social problems of social development, the influence of state financial support in the countries of the European Union (EU), and also determined the common features and differences of state regulation of entrepreneurship.…”
Section: Discussionmentioning
confidence: 99%
“…The essence of the financial security concept and the task of the financial security-ensuring system in this case is the ability of the enterprise to function effectively and provide an increase in competitive positions on the market. Supporters of this approach [6][7][8][9][10][11][12][13][14] define the criterion of financial security as the achievement of the enterprise's goal.…”
Section: Introductionmentioning
confidence: 99%